Assessment of polytetrafluoroethylene composites for deep groove ball bearing applications through free run and rolling contact fatigue tests - Dhruv Deshwal; Sachin U. Belgamwar; Siddappa I. Bekinal (Scientific Reports)
Abstract Polytetrafluoroethylene (PTFE) is widely used in tribological applications. However, its usage in the ball-bearing application has not been explored. The present study investigates the usage of PTFE composites for deep groove ball (DGB) bearings. Initially, a ball-on-disc experiment is conducted to analyze the interaction between pure PTFE, 40% bronze-filled, 25% glass fiber-filled PTFE composites, and Si3N4 balls by determining the coefficient of friction (COF) and specific wear rate. Then, the reliability of the fabricated DGB is checked through free run and rolling contact fatigue (RCF) tests using a 6-channel DAQ system (OR35-INST). In the free run test, a rotor supported on fabricated polymer bearing sets is rotated up to two million cycles under minimal load conditions. Its vibrational signals and RPM are continuously monitored through an accelerometer and tachometer. After a subsequent number of cycles, the dynamic characteristics of the shaft are recorded using the DAQ system and eddy probes. Finally, an RCF test is conducted to check the load-bearing capacity of the bearing. The bearing is subjected to a 36 N to 108 N (in step of 36 N) load, and the vibration signals are recorded.